Analytical study on changes in domestic hot water use caused by COVID-19 pandemic. (15th September 2021) - Kim, Dongwoo; Yim, Taesu; Lee, Jae Yong
Abstract: COVID-19 made considerable changes in the lifestyle of people, which have led to a rise in energy use in homes. So, this study investigated the relationship between COVID-19 and domestic hot water demands. For this purpose, a nondimensional and principal component analysis were conducted to find out the influencing factors using demand data before and after COVID-19 from our study site. Analysis showed that the COVID-19 outbreak affected the daily peak time and the amount of domestic hot water usage, the active case number of COVID-19 was a good indicator for correlating the changes in hot water demand and patterns. Based on this, a machine learning model with an artificial neural network was developed to predict hot water demand depending on the severity of COVID-19 and the relevant correlation was also derived. The model analysis showed that the increase in the number of active cases in the region affected the hot water demand increased at a certain rate and the maximum demand peak in morning during weekdays and weekends decreased. Furthermore, if the number of active cases reached more than 4000, the peak in morning moved to afternoon so that the energy use patterns of weekdays and weekends are assimilated. Highlights: COVID-19 increased the hot water demand in the residential sector by 8.08–16.41%. The hot water demand can be predicted based on the COVID-19 active cases. Machine learning model can predict hourly demand with an accuracy of R 2  = 0.9749. The daily hot water pattern shifts along the number of the COVID-19 active cases.